Production of biodiesel from babassu oil using methanol-ethanol blends - Silva, Fernando Carvalho; Cavalcante, Kiany Sirley Brandão; Louzeiro, Hilton Costa; Moura, Katia Regina Marques; Maciel, Adeilton Pereira; Soledade, Luiz Edmundo Bastos; Souza, Antonio Gouveia (Eclética Química, 2010)
Maranhão state in Brazil presents a big potential for the cultivation of several oleaginous species, such as babassu, soybean, castor oil plant, etc... These vegetable oils can be transformed into biodiesel by the transesterification reaction in an alkaline medium, using methanol or ethanol. The biodiesel production from a blend of these alcohols is a way of adding the technical and economical advantages of methanol to the environmental advantages of ethanol. The optimized alcohol blend was observed to be a methanol/ethanol volume ratio of 80 % MeOH: 20 % EtOH. The ester content was of 98.70 %, a value higher than the target of the ANP, 96.5 % (m/m), and the biodiesel mass yield was of 95.32 %. This biodiesel fulfills the specifications of moisture, specific gravity, kinematic viscosity and percentages of free alcohols (methanol plus ethanol) and free glycerin.